Effect of caregiving at end of life on grief, quality of life and general health: A prospective, longitudinal, comparative study - Breen, Lauren; Aoun, S.; O’Connor, Moira; Johnson, Andrew; Howting, D. (SAGE PUBLICATIONS LTD, 2019)
© The Author(s) 2019. Background: Determining the effect of caregiving and bereavement remains a challenge. To date, no study has employed a comparison group to investigate caregivers’ grief, quality of life and general health in relation to non-caregivers. Aim: We aimed to determine how caregivers’ grief, quality of life and general health changed following death compared to non-caregivers and whether pre-death grief predicted these outcomes. Design: A prospective, longitudinal study of family caregivers and a comparison group matched for age, gender and postcode was conducted. All participants completed questionnaires at four points – once pre-death and three times post-death (3–4 months, 6–7 months and 9–10 months). Setting/participants: Participants (N = 70) were family caregivers of persons receiving palliative care, mostly for cancer, recruited from three palliative care providers in Western Australia and matched comparisons recruited from advertisements. Results: There were significant differences between the caregivers’ and comparisons’ grief, general health and quality of life at pre-death, 3–4 months and 6–7 months post-death, but not at 9–10 months post-death. The rate of progression in these constructs following death was independent from the intensity of pre-death grief. However, caregiver prolonged grief score significantly predicted prolonged grief score at 6–7 and 9–10 months post-death. Conclusion: It took 9–10 months for the caregivers’ grief, general health and quality of life to correspond to the comparison group. These findings present an opportunity for palliative care research and practice to consider how best to support the majority of caregivers without grief complications so that their pre- and post-death support needs are realised.